(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article discusses the importance of the nursing process in maintaining and improving the mental health of the population. It highlights the role of nurses in assessing patients’ psychological conditions, identifying mental health problems, planning appropriate care, implementing nursing interventions, and evaluating treatment outcomes. The study emphasizes the significance of effective communication, psychological support, preventive measures, and community-based healthcare services in promoting mental well-being. Furthermore, the article examines modern approaches and strategies used in nursing practice to enhance the quality of mental healthcare services.